Alternative Data Governance Models: Moving Beyond One-Size-Fits-All Solutions - Bruno Carballa Smichowski (Intereconomics, 2019)
Data governance is currently dominated by the hegemonicmodel in which the data collector retains exclusive controlover the data it collects. The overreach of this model has created problems in various fields that call for alternativedata governance models
Keywords: 330